2006
DOI: 10.1597/04-006.1
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Preoperative Use of an Orthopedic Plate on Articulatory Function in Children with Cleft Lip and Palate

Abstract: Continuous use of the OP up to the time of palatoplasty appeared to be effective for the postoperative articulatory function in children with complete cleft lip and palate. Inhibiting irregular movements of the tongue, the OP might assist in preventing "palatalized articulation."

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 26 publications
1
5
0
2
Order By: Relevance
“…12 PSO is often reasoned by the postulate that the tongue of CLP newborns needs to be trained to maintain a posture considered to be physiological in order to support normal language development: Based on sonography analyses of tongue movements and postoperative articulatory function in CLP children aged about 5 years, Suzuki et al concluded that those subjects could not create negative pressure in the oral cavity, regardless of previous presence or absence of an orthopedic plate. 25 This finding is confirmed by the results of our study (Table 3). However, they also reported an improvement in tongue dynamics during sucking and articulation in subjects treated by PSO, which was not substantiated by our results (Table 2-5).…”
Section: Potential Benefits Of Psosupporting
confidence: 90%
“…12 PSO is often reasoned by the postulate that the tongue of CLP newborns needs to be trained to maintain a posture considered to be physiological in order to support normal language development: Based on sonography analyses of tongue movements and postoperative articulatory function in CLP children aged about 5 years, Suzuki et al concluded that those subjects could not create negative pressure in the oral cavity, regardless of previous presence or absence of an orthopedic plate. 25 This finding is confirmed by the results of our study (Table 3). However, they also reported an improvement in tongue dynamics during sucking and articulation in subjects treated by PSO, which was not substantiated by our results (Table 2-5).…”
Section: Potential Benefits Of Psosupporting
confidence: 90%
“…When considering the treatment or prevention of palatalized articulation based on the findings of the present study, a presurgical orthopedic may play a role in improving abnormal morphology of the palate 19,20 . In our previous study on the incidence of palatalized articulation relating to treatment using a Hotz plate 21 , it was suggested that the Hotz plate improved abnormal palatal morphologies and might decrease the occurrence of palatal articulation.…”
Section: Discussionmentioning
confidence: 88%
“…1 Moreover, the HP is effective for improving postoperative articulatory function. 6 Recently, presurgical nasoalveolar molding (NAM) was also introduced for the preoperative correction of nasal deformities. 19 This is an effective adjunctive therapy for correcting nasal deformities both preoperatively and postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Furthermore, continuous use of the HP until the time of palatoplasty seems to be effective for improving postoperative articulatory function. 6 Preoperative treatment with the HP causes the dimensions of the upper part of the oral cavity of an infant with unilateral complete cleft lip and palate (UCLP) to approach those of infants without a cleft. 7 Millard 8 also reported that presurgical orthopedics can be of great value in aligning the cleft alveolus, reducing the width of the cleft, and correcting the depression of the cleft alar base.…”
mentioning
confidence: 99%